Daunting Problems of Micro, Small, and Medium Enterprises (MSMEs) in India: An Entrepreneurial Perception - Kishore Somalaraju; Himachalam Dasaraju (International Journal of Small and Medium Enterprises and Business Sustainability, 2020)
This paper purports to review the importance, progress, and major issues being faced by micro, small, and medium enterprises (MSMEs) and the perception of entrepreneurs based on empirical study. It has been recognized as an engine of economic growth and lifeline of the Indian economy owing to its inherent features of potential for huge employment generation, lower investment, low cost of capital, economic stimulation, empowerment and wellbeing of rural people. The Government has taken several measures to promote MSMEs by starting various flagship programs and initiatives. Besides the promotional measures of the Government, the MSMEs sector is not free from problems due to various reasons. Hence, it calls for an empirical study to probe into various problems being confronted by the entrepreneurs and their perception. The study adopted an empirical survey method with 296 sample entrepreneurs. The primary data are used mainly for analyzing the problems in different aspects namely financial, operational, infrastructural, labour, marketing, and raw material problems and the perceptions of sample entrepreneurs in Chittoor District of Andhra Pradesh. The study observed that apart from the usual problems as mentioned earlier, this sector is suffering from the inability to adopt new technology, global competitiveness, and access to global markets, which are dire need of the day to be addressed. The present global Covid-19 pandemic lockdown for more than 2 months has disrupted the functioning of MSMEs very badly and it requires robust policy measure to bring back into normalcy